2021
DOI: 10.12688/wellcomeopenres.16168.1
|View full text |Cite
|
Sign up to set email alerts
|

An open dataset of Plasmodium falciparum genome variation in 7,000 worldwide samples

Abstract: MalariaGEN is a data-sharing network that enables groups around the world to work together on the genomic epidemiology of malaria. Here we describe a new release of curated genome variation data on 7,000 Plasmodium falciparum samples from MalariaGEN partner studies in 28 malaria-endemic countries. High-quality genotype calls on 3 million single nucleotide polymorphisms (SNPs) and short indels were produced using a standardised analysis pipeline. Copy number variants associated with drug resistance and structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(68 citation statements)
references
References 95 publications
0
65
0
Order By: Relevance
“…In brief, we sequenced the P. falciparum genome using the Illumina × Ten platform using two approaches based on sequencing whole DNA and selective whole genome amplification 7 . We used an established pipeline 8 to identify and call genotypes at over 2 million single nucleotide polymorphisms (SNPs) and short insertion/deletion variants across the Pf genome in these samples ( Methods ). The following analysis is based on 4,171 samples that had high quality data for both parasite and human genotypes and were not closely related, of which a subset of 3,346 had human genome-wide genotyping available.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…In brief, we sequenced the P. falciparum genome using the Illumina × Ten platform using two approaches based on sequencing whole DNA and selective whole genome amplification 7 . We used an established pipeline 8 to identify and call genotypes at over 2 million single nucleotide polymorphisms (SNPs) and short insertion/deletion variants across the Pf genome in these samples ( Methods ). The following analysis is based on 4,171 samples that had high quality data for both parasite and human genotypes and were not closely related, of which a subset of 3,346 had human genome-wide genotyping available.…”
Section: Main Textmentioning
confidence: 99%
“…The Pfsa1 +, Pfsa2 + and Pfsa3 + alleles had similar frequencies in Kenya (approximately 10-20%) whereas in Gambia Pfsa2 + had a much lower allele frequency than Pfsa1 + or Pfsa3 + (< 3% in all years studied, versus 25-60% for the Pfsa1 + or Pfsa3 + alleles; Figure 3a and Supplementary Figure 9 ). To explore the population genetic features of these loci in more detail, we analysed the MalariaGEN Pf6 open resource which gives P. falciparum genome variation data for 7,000 worldwide samples 8 ( Figure 3b ). This showed considerable variation in the frequency of these alleles across Africa, the maximum observed value being 61% for > Pfsa3 + in the Democratic Republic of Congo, and indicated that these alleles are rare outside Africa.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…For an excellent review of malaria population genomics, see [46]. The large-scale data-sharing Malaria Genomic Epidemiology Network (MalariaGEN) has made available thousands of parasite genomes-7000 P. falciparum genomes from 28 countries at the time of writing-to the research community [47,48]. The data provide an unprecedented snapshot of P. falciparum population genetics and the asso-ciated advances in sample preparation, sequencing technology, analysis methods and data sharing lay the foundations to more fully integrate genomics into disease epidemiology, though technical challenges remain [49,50].…”
Section: The Variable Genome: Genomic Diversity Within Plasmodium Speciesmentioning
confidence: 99%
“…For example, extensive outcrossing occurs in many parts of sub-Saharan differing treatment regimes (the pill). Below the map is a schematic population structure tree based on genome-wide variation data, after [48]. (Regional populations are indicated at the tips of the tree: SAm = South America; WA = West Africa; CA = Central Africa; EA = East Africa; SAs = South Asia; SEA,W = South East Asia, West; SEA,W = South East Asia, East; O = Oceania).…”
Section: Figure 2 Plasmodium Falciparum Population Genomics (A)mentioning
confidence: 99%